Relationship Between Chronotype, Social Jetlag, Attention Control, and Academic Achievement in Nursing Students During the COVID-19 Pandemic - Nazmiye Çıray; Meltem Adaiçi; Aybüke Özcan (Türk Uyku Tıbbı Dergisi, 2023)

(untitled)
Objective:This study aimed to examine the relationship between chronotype, social jetlag, attention control, and academic performance in nursing students during the Coronavirus disease-2019 pandemic.Materials and Methods:The descriptive study was conducted online with undergraduate nursing students (n=405) who were members of the Student Nurses Association and volunteered to participate in the study between July 2021 and April 2022. In collecting the data of the research, students’ academic performance information and sociodemographic data that may affect their chronotype were evaluated using the Student Information Form. In addition, the Social Jetlag Form, Morning Evening Scale, and Attention Control Scale were used for evaluation.Results:The mean age of the students participating in the study was 20.29±0.91, 75.8% were female and 41.5% were freshmen. When the chronotypes of the students were examined, it was observed that 18.0% of them were morning-type, 68.6% of them were intermediate -type, and 13.4% of them were evening-type. When the chronotype characteristics of the students, their weighted passing grade, attention control point average, and weekday sleep duration were examined, no significant difference was observed between them (p>0.05). However, when the average of social jetlag hours was compared according to chronotypes, a statistically significant difference was found (p<0.05). Social jetlag values of morning students were found to be significantly lower than those in the evening and intermediate students. The social jetlag values in the intermediate type.Conclusion:There is no significant relationship between social jetlag and chronotype variables, attention control, and academic performance in the post-pandemic period. It can be said that students with an evening type chronotype and creating their own timelines for the social jetlag value create a positive change. However, in the new post-pandemic period, this seemingly positive change is thought to have negative consequences in terms of the adaptation of university students to the new normal. Further studies are needed on the changes in chronotypes in the post-pandemic period.